2016
DOI: 10.1097/bot.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Preoperative Deep Vein Thrombosis in Calcaneal Fractures

Abstract: Objectives: This study examined the incidence and risk factors of preoperative deep vein thrombosis (DVT) in patients presenting to an outpatient setting with an isolated calcaneal fracture. Design: Retrospective chart reviewSetting: All patients included in the study presented to the treating surgeon at a Level I trauma center with isolated calcaneal fractures as an outpatient between 2005-2013.Methods: These patients were either referred from outside hospitals, had been evaluated in the emergency department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…In the present study, patients with lower extremity fractures at the age of > 60 years were found to have the highest incidence of DVT (6.6%), and this was similar to the ndings of Williams et al [7] . In the opinion of the present authors, there are more internal diseases in elderly patients, which results in a longer preparation time for surgery and longer preoperative resting time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, patients with lower extremity fractures at the age of > 60 years were found to have the highest incidence of DVT (6.6%), and this was similar to the ndings of Williams et al [7] . In the opinion of the present authors, there are more internal diseases in elderly patients, which results in a longer preparation time for surgery and longer preoperative resting time.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a previous study has shown that DVT is most common in middle-aged patients with lower extremity fractures, but there is no difference in its incidence between sexes [4] . Different from the results of that study, Williams et al suggested that older age is a risk factor for DVT [7] . In a study involving 829 patients, the incidences of DVT in patients with hip, femur shaft, knee, lower leg, and foot or ankle fractures were found to be 16.7%, 12.2%, 9%, 3.7%, and 2.3%, respectively [8] .…”
Section: Introductioncontrasting
confidence: 70%
“…In a study of one hundred fifty-nine patients, Williams suggested that older age was a risk factor for DVT, but body mass index and sex were not significant predictors. 9 In another study of nine hundred one consecutive patients, Park 10 suggested an advanced age, cardiovascular disease, and chronic lung disease were independent risk factors.Michetti 11 and Chen 12 also analyzed the risk factors of DVT in fracture patients. However, there were controversial conclusions in studies, and it is necessary to perform more studies to clarify these issues.…”
Section: Introductionmentioning
confidence: 98%
“…Extensive and deep understanding the epidemiologic characteristics of DVT, particularly the relevant risk factors, was of extreme importance in prevention of this key adverse event. By far, multiple risk factors associated with DVT have been identified, including advanced age, male gender, obesity, a history of DVT or pulmonary embolism, immobility, smoking or fracture itself [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%